Human mitochondrial carnitine acylcarnitine carrier: Molecular target of dietary bioactive polyphenols from sweet cherry (Prunus avium L.). (1st July 2019) - Console, Lara; Giangregorio, Nicola; Cellamare, Saverio; Bolognino, Isabella; Palasciano, Marino; Indiveri, Cesare; Incampo, Giovanna; Campana, Sabrina; Tonazzi, Annamaria
Abstract: The effect of polyphenols, recognized as the principal antioxidant and beneficial molecules introduced with the diet, extracted from sweet cherry ( Prunus avium L.) on the recombinant human mitochondrial carnitine/acylcarnitine transporter (CACT) has been studied in proteoliposomes. CACT transport activity, which was strongly impaired after oxidation by atmospheric O2 or H2 O2, due to the formation of a disulfide bridge between cysteines 136 and 155, was restored by externally added polyphenols. CACT reduction by polyphenols was time dependent. Spectroscopic analysis of polyphenolic extracts revealed eight most represented compounds in four cultivars. Molecular docking of CACT structural omology model with the most either abundant and arguably bio-available phenolic compound (trans 3-O-feruloyl-quinic acid) of the mix, is in agreement with the experimental data since it results located in the active site close to cysteine 136 at the bottom of the translocation aqueous cavity. Graphical abstract: Image 1 Highlights: Polyphenols from vegetal sources have an acknowledged antioxidant activity. Mitochondrial carnitine carrier is crucial for human bioenergetics and is inactivated by oxidation. Polyphenols extracted from sweet cherry restore the human mitochondrial carnitine carrier activity after oxidative injury.